Low-dose ganciclovir ameliorates dextran sulfate sodium-induced ulcerative colitis through inhibiting macrophage STING activation in mice - Gong, Lin-Kong; Yang, Xiaodong; Yang, Juan; Wu, Shu; Chen, Yue; Zhang, Jiang-Tao; Wang, Zhi-Hong; Chen, Li-Hua; Xing, Chungen; Liu, Tong (Frontiers in Pharmacology, 2022)
Ganciclovir (GCV) is a prodrug nucleoside analogue and is clinically used as antiviral drug for the treatment of cytomegalovirus (CMV) and other infections. Based on the potential anti-inflammatory activity of GCV, this study aimed to investigate the therapeutic effects of ganciclovir on dextran sulfate sodium (DSS)-induced ulcerative colitis (UC), which may involve cyclic GMP-AMP synthase (cGAS)-stimulator of interferon genes (STING) pathways. Our results demonstrated that incubation of GCV (50 μM) inhibited cGAS-STING pathway in macrophage RAW264.7 cells. Then, it was found that intestinal cGAS-STING pathways were upregulated in UC patients, Crohn’s disease colitis (CD) patients, and DSS-induced colitis mice. Intraperitoneal injection of low-dose GCV (10 mg/kg/day) attenuated DSS-induced colitis and abdominal pain in mice. GCV treatment significantly inhibited the upregulation of cGAS-STING pathway in DSS-induced colitis mice. Moreover, DSS-induced colitis and gut dysbiosis was markedly attenuated in STING deficient mice compared with that of wild-type (WT) mice. Finally, there was lacking therapeutic effect of GCV on DSS-induced colitis in STING deficient mice. Together, our results indicated that low-dose GCV ameliorated DSS-induced UC in mice, possibly through inhibiting STING signaling in colonic macrophages, indicating that GCV may be useful for the treatment of UC.